(3GdbQGfGJ hJMhjd GdSfjfs - (3GdWHQj , YeQ Hf GdaQNGf GdWHQj, CHhMfaj,J (B200 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI deG QCjJ eG jLQi Ydi ef hVY GdcJH ai GdbQGfGJ hJMGhjd GdSfjf hCehQ GdOhd hGdedhc s
(3BNQgG (B:s
(3hEPG SbWJ GdSYhO hGSJhdJ GdfMhS Od Pdc Ydi GdaSGO hGdVQQ ef bjd Jdc GdQjGM HEPf Gddg Je GdLRA GdNGeS ef cJGH GdbQGfGJ hJMhjd GdSfjf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B304s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B80 s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYg GSJGfHhd (B(2/315) s
Keywords: (3Gdadcs